Got the look - Grippando, James, 1958- (New York : HarperTorch, 2006)
After his girlfriend is kidnapped, Miami attorney Jack Swyteck discovers that she is married to a wealthy man who has received a ransom demand, pitting Jack against a killer who is so fiendishly clever that even Jack may have met his match.
New York
Keywords: Swyteck, Jack (Fictitious character) -- Fiction; Attorney and client -- Fiction